Intussusception After Pancreaticoduodenectomy. Issue 5 (May 2019) - Patel, Kishan; Luthra, Anjuli; Aberra, Fasika; Lara, Luis F.; Gray, Darrell
Abstract : ABSTRACT: Intussusception after pancreaticoduodenectomy (Whipple procedure) is exceedingly rare. We present a case of retrograde jejunal intussusception into the gastric lumen in a patient who previously underwent Whipple procedure. Diagnostic endoscopy may serve to confirm intussusception, identify a potential lead point, and, in some cases, endoscopically reduce the intussusception. Ultimately, however, surgical management is recommended due to a high rate of recurrence along with the potential to detect a lead point and associated malignancy.